Mesoporous composite alumina carrier as well as preparation method and application thereof

By mixing aluminum acetylacetonate and zinc acetate with aluminum sol and composite template agent, a mesoporous composite alumina support with high specific surface area and flexible acid-base center is prepared, which solves the problems of insufficient specific surface area of ​​the existing alumina support and complex preparation methods, and improves the catalytic performance.

CN119897083APending Publication Date: 2025-04-29YUEYANG KAIDA TECH DEV CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510075684.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-17
Publication Date
2025-04-29

AI Technical Summary

Technical Problem

The specific surface area of ​​the existing alumina carrier is difficult to exceed 250m2/g, the preparation method is complex and requires a variety of reagents, and the acid-base center distribution regulation is inflexible, resulting in poor adaptability in hydrogenation or dehydrogenation reactions.

Method used

By dissolving aluminum acetylacetone and zinc acetate in an alcohol solvent, mixing with aluminum sol, alkyl glucoside, alkyl diesteryl quaternary ammonium salt and other components, it is crystallized to obtain a mesoporous composite alumina support with a specific surface area of ​​more than 250 m2/g and flexible and adjustable acid-base center.

Benefits of technology

The efficient preparation of mesoporous composite alumina support with high specific surface area, large pore volume and flexible acid-base is achieved, and the catalytic performance of the support in reactions such as alkane dehydrogenation and olefin saturated hydrogenation are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119897083A_ABST
    Figure CN119897083A_ABST
Patent Text Reader

Abstract

The invention provides a mesoporous composite alumina carrier as well as a preparation method and application thereof. The preparation method of the mesoporous composite alumina carrier comprises the following steps: dissolving aluminum acetylacetonate and zinc acetate in an alcohol solvent to obtain a solution A; dissolving alkyl glucoside and alkyl diester quaternary ammonium salt in water to obtain a solution B; crystallizing the alumina sol and the solution A in the solution B at the same time to prepare alumina carrier raw powder; and carrying out post-treatment on the alumina carrier raw powder to obtain the mesoporous composite alumina carrier. The preparation method of the mesoporous composite alumina carrier can simply and efficiently prepare the alumina carrier with the specific surface area of more than 250m < 2 > / g, flexible and adjustable acid-base center and large mesoporous volume ratio without using an acid-base reagent.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of catalyst synthesis and application, and specifically relates to a mesoporous composite alumina carrier and a preparation method and application thereof. Background Art

[0002] Alumina carriers are widely used in hydrogenation and dehydrogenation reactions. Generally, alumina carriers are made from bauxite or aluminate, with a specific surface area of ​​no more than 150m 2 / g. Alumina carriers with developed pore structures and high specific surface area can facilitate metal loading, reaction and mass transfer processes, and therefore have always attracted the attention of researchers and industry.

[0003] CN108640132A discloses a macroporous and mesoporous alumina carrier and its preparation method and use. By using P123 as a template and adding citric acid, concentrated hydrochloric acid and other reagents to synthesize a three-dimensional ordered macroporous-mesoporous alumina carrier with uniform pore size, it can be applied to the field of immobilized enzymes. CN108862345A discloses a preparation method of high specific surface area mesoporous alumina. In the process, glucose, polyallylamine, sodium borohydride, polyethylene glycol, succinic anhydride and chloroform are needed to prepare an alumina carrier with high porosity and large specific surface area.

[0004] The specific surface area of ​​the alumina carrier currently prepared is difficult to exceed 250m 2 / g, and the existing preparation method requires the use of multiple reagents, which is relatively cumbersome and has almost no regulatory effect on the acid center distribution of the alumina carrier, which makes it difficult for the final carrier to have good adaptability in hydrogenation or dehydrogenation reactions.

[0005] Based on this, it is still necessary to study new alumina carrier preparation technology solutions that can simply and efficiently prepare alumina with a specific surface area of ​​250m 2 / g or more, with flexibly adjustable acid-base centers and a large proportion of mesoporous pore volume. Summary of the invention

[0006] The purpose of the present invention is to provide a method for simply and efficiently preparing a specific surface area of ​​250 m 2 A technical solution for an alumina carrier with more than / g, flexibly adjustable acid-base centers, and a large proportion of mesoporous pore volume.

[0007] In order to achieve the above object, the present invention provides the following technical solutions.

[0008] In a first aspect, the present invention provides a method for preparing a mesoporous composite alumina carrier, wherein the method comprises:

[0009] Aluminum acetylacetonate and zinc acetate are dissolved in an alcohol solvent to obtain solution A;

[0010] Dissolving alkyl glucoside and alkyl diester quaternary ammonium salt in water to obtain solution B;

[0011] Adding aluminum sol and solution A to solution B simultaneously for crystallization to prepare alumina carrier raw powder;

[0012] The raw powder of alumina carrier is post-treated to obtain a mesoporous composite alumina carrier.

[0013] The preparation method of the mesoporous composite alumina carrier provided by the present invention can simply and efficiently prepare a mesoporous composite alumina carrier with a specific surface area of ​​250m without using acid or alkali reagents. 2 / g or more, with flexibly adjustable acid-base centers and a large proportion of mesoporous pore volume.

[0014] According to a preferred embodiment of the first aspect, preferably, the alcohol solvent is methanol or ethanol; more preferably, the alcohol solvent is ethanol.

[0015] According to a preferred embodiment of the first aspect, preferably, the mass ratio of aluminum acetylacetonate, zinc acetate, alcohol solvent, alkyl glucoside, alkyl diester quaternary ammonium salt, aluminum sol and water is: aluminum acetylacetonate: zinc acetate: alcohol solvent: alkyl glucoside: alkyl diester quaternary ammonium salt: aluminum sol: water = 1: (0.01-0.5): (50-150): (0.005-0.1): (0.005-0.1): (10-500): (50-200).

[0016] According to a preferred embodiment of the first aspect, preferably, the mass content of aluminum oxide in the aluminum sol is 10-50%.

[0017] According to a preferred embodiment of the first aspect, preferably, the pH value of the aluminum sol is 2-5.

[0018] According to a preferred embodiment of the first aspect, preferably, the particle size of the aluminum sol is 10-40 nm.

[0019] According to a preferred embodiment of the first aspect, preferably, the alkyl group of the alkyl glucoside is a C8-C18 chain alkyl group;

[0020] More preferably, the alkyl glucoside is selected from at least one of hexyl glucoside and octyl glucoside.

[0021] According to a preferred embodiment of the first aspect, preferably, the alkyl group of the alkyl diester quaternary ammonium salt is a C8-C18 chain alkyl group;

[0022] More preferably, the alkyl diester-based quaternary ammonium salt is selected from at least one of dodecyl diester-based quaternary ammonium salt, tetradecyl diester-based quaternary ammonium salt, and hexadecyl diester-based quaternary ammonium salt.

[0023] According to a preferred embodiment of the first aspect, preferably, the process of simultaneously adding the aluminum sol and solution A to solution B for crystallization to prepare the alumina carrier raw powder comprises:

[0024] Add aluminum sol and solution A to solution B simultaneously under stirring conditions, heat and stir to obtain a mixed solution;

[0025] The mixed solution is subjected to crystallization treatment;

[0026] The product obtained by the crystallization treatment is cooled and then solid-liquid separation is performed, and the obtained solid phase is the original powder of the alumina carrier;

[0027] More preferably, the temperature of the heating and stirring is 60-80°C;

[0028] More preferably, the heating and stirring time is 4-20 hours;

[0029] More preferably, the stirring speed of the heating stirring is 200-1000 r / min;

[0030] More preferably, when the aluminum sol and solution A are added to solution B simultaneously under stirring conditions, the stirring speed is 600-1000 r / min.

[0031] According to a preferred embodiment of the first aspect, preferably, the crystallization temperature is 100-250°C.

[0032] According to a preferred embodiment of the first aspect, preferably, the crystallization time is 6-72 hours.

[0033] According to a preferred embodiment of the first aspect, preferably, post-processing the original powder of the alumina carrier to obtain the mesoporous composite alumina carrier comprises:

[0034] The alumina carrier raw powder is washed, dried and calcined in sequence to obtain a mesoporous composite alumina carrier;

[0035] More preferably, the molding process is performed after drying and before calcining;

[0036] More preferably, the drying temperature is 80-150°C;

[0037] More preferably, the drying time is 6-20 hours;

[0038] More preferably, the calcination temperature is 450-600°C;

[0039] More preferably, the calcination time is 4-10 hours;

[0040] More preferably, the calcination atmosphere is an air atmosphere.

[0041] In a second aspect, the present invention provides a mesoporous composite alumina carrier, which can be prepared by the preparation method of the mesoporous composite alumina carrier provided in the first aspect.

[0042] In a third aspect, the present invention provides the use of the mesoporous composite alumina carrier provided in the second aspect in alkane dehydrogenation and olefin saturation hydrogenation.

[0043] In the technical solution provided by the present invention, the raw material of the alumina carrier is mainly aluminum sol, and a small amount of aluminum acetate acetonate and zinc acetate are used to adjust the surface acidity and alkalinity. No acid-base compounds are needed in the preparation process, and the preparation process is simple.

[0044] Compared with the existing technology, it has the following advantages:

[0045] 1. Make full use of the differences in the properties of aluminum acetylacetonate, zinc acetate and aluminum sol raw materials. Use alcohol solvent to dissolve aluminum acetylacetonate and zinc acetate first, mix them evenly, and then pour them into the solution of the composite template together with the aluminum sol. Aluminum acetylacetonate and zinc acetate will preferentially interact with the composite template and evenly distribute on the surface of the alumina particles in the aluminum sol during the crystallization process. After calcination, they can form evenly distributed acid centers and alkaline centers on the surface of the carrier pores, and the acidity and alkalinity of the carrier can be flexibly adjusted.

[0046] 2. Special composite templates are used in the preparation process, including alkyl glucoside and alkyl diester quaternary ammonium salt.

[0047] As a component of the composite template, alkyl glucoside plays many prominent roles in the synthesis process: on the one hand, the polyhydroxy structure it contains can directly interact with aluminum acetylacetonate and zinc acetate in the solution to achieve the effect of uniform distribution of aluminum and zinc ions; on the other hand, the polyhydroxy structure it contains can also interact with the aluminum hydroxyl groups on the surface of alumina particles in aluminum sol, so that the surface of alumina particles can adsorb free aluminum and zinc through compounding with alkyl glucoside.

[0048] As another component of the composite template, the alkyl diester quaternary ammonium salt can play an important role in inhibiting the aggregation of alumina particles, improving the dispersion of free aluminum and zinc, and increasing the specific surface area of ​​the carrier: first, the alkyl diester quaternary ammonium salt can play a compounding role with the alkyl glucoside through the alkyl and ester groups, and the two can form a unique structure of alternating arrangement through the compounding effect, which can further improve the dispersion of free aluminum and zinc and prevent the aggregation of aluminum or zinc on the surface of the carrier after calcination; secondly, the quaternary ammonium cation of the alkyl diester quaternary ammonium salt can effectively prevent the aggregation of alumina particles in the aluminum sol through the charge effect; thirdly, the alkyl diester quaternary ammonium salt can act as a pore-forming agent together with the alkyl glucoside to effectively increase the specific surface area and pore volume of the alumina carrier after calcination.

[0049] 3. The composite alumina carrier prepared by the technical solution of the present invention has the characteristics of large specific surface area, high pore volume, flexible adjustment of surface acidity and alkalinity, and stable structure. It can give full play to the characteristics of rapid mass transfer, inhibit the sintering and deactivation of precious metal active components such as platinum, and improve reaction stability in the application process of alkane dehydrogenation and olefin saturation hydrogenation, thereby showing excellent catalytic performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0050] Figure 1 This is a transmission electron micrograph of the mesoporous composite alumina carrier in Example 1.

[0051] Figure 2 This is a transmission electron microscopy image of the mesoporous composite alumina carrier in Comparative Example 3.

[0052] Figure 3 The XRD spectra of the mesoporous composite alumina carriers in Example 1 and Comparative Example 3 are shown.

[0053] Figure 4 These are the XRD spectra of the mesoporous composite alumina supports in Examples 1, 2, 3, and 4. DETAILED DESCRIPTION

[0054] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work belong to the protection scope of the present invention.

[0055] Example 1

[0056] This embodiment provides a mesoporous composite alumina carrier.

[0057] The mesoporous composite alumina carrier provided in this embodiment is prepared by the following preparation method:

[0058] Weigh 1.00 g of aluminum acetylacetonate and 0.02 g of anhydrous zinc acetate compound, dissolve them in 100 g of ethanol in sequence, stir evenly until the solution becomes clear, and prepare solution A;

[0059] Weigh 0.1 g of octyl glucoside and 0.1 g of octadecyl diacetyl ammonium chloride (purchased from Henan Daochun New Material Technology Co., Ltd., model YH-866) and dissolve them in 50 g of deionized water until they are completely dissolved, thereby preparing a solution B;

[0060] Under stirring conditions (speed of 600 rpm), 500 g of aluminum sol (BRD-300A nano aluminum sol produced by Suzhou Baird New Material Technology Co., Ltd., with an aluminum oxide mass content of 20%, a pH value of 2-5, and a particle size of 10-40 nm) and the solution A obtained in the first step were added to the solution B, and the mixture was heated to 70° C. and stirred (speed of 600 rpm) for 10 hours to obtain a mixed solution;

[0061] The stirred mixed solution was transferred into a crystallization kettle, crystallized at 200°C for 10 hours, taken out, quenched, and filtered to obtain the original alumina carrier powder;

[0062] The alumina carrier raw powder was washed, dried in a drying oven at 100°C for 10 hours, and calcined in air atmosphere at 500°C for 4 hours to obtain a mesoporous composite alumina carrier.

[0063] The specific surface area and pore volume of the mesoporous composite alumina carrier prepared in this example are shown in Table 1.

[0064] Comparative Example 1

[0065] This comparative example provides a mesoporous composite alumina carrier.

[0066] The preparation method of the mesoporous composite alumina carrier provided in this comparative example is different from that in Example 1 in that no octyl glucoside is added. The mesoporous composite alumina carrier is prepared by the following preparation method:

[0067] Weigh 1.00 g of aluminum acetylacetonate and 0.02 g of anhydrous zinc acetate compound, dissolve them in 100 g of ethanol in sequence, stir evenly until the solution becomes clear, and prepare solution A;

[0068] Weigh 0.1 g of octadecyl diester ammonium chloride (purchased from Henan Daochun New Material Technology Co., Ltd., model YH-866) and dissolve it in 50 g of deionized water until it is completely dissolved to prepare a solution B;

[0069] Under stirring conditions (speed of 600 rpm), 500 g of aluminum sol (BRD-300A nano aluminum sol produced by Suzhou Baird New Material Technology Co., Ltd., with an aluminum oxide mass content of 20%, a pH value of 2-5, and a particle size of 10-40 nm) and the solution A obtained in the first step were added to the solution B, and the mixture was heated to 70° C. and stirred (speed of 600 rpm) for 10 hours to obtain a mixed solution;

[0070] The stirred mixed solution was transferred into a crystallization kettle, crystallized at 200°C for 10 hours, taken out, quenched, and filtered to obtain the original alumina carrier powder;

[0071] The alumina carrier raw powder was washed, dried in a drying oven at 100°C for 10 hours, and calcined in air atmosphere at 500°C for 4 hours to obtain a mesoporous composite alumina carrier.

[0072] The specific surface area and pore volume of the mesoporous composite alumina carrier prepared in this comparative example are shown in Table 1.

[0073] Comparative Example 2

[0074] This comparative example provides a mesoporous composite alumina carrier.

[0075] The preparation method of the mesoporous composite alumina carrier provided in this comparative example is different from that in Example 1 in that no octadecyl diester ammonium chloride (purchased from Henan Daochun New Material Technology Co., Ltd., model YH-866) is added. The mesoporous composite alumina carrier is prepared by the following preparation method:

[0076] Weigh 1.00 g of aluminum acetylacetonate and 0.02 g of anhydrous zinc acetate compound, dissolve them in 100 g of ethanol in sequence, stir evenly until the solution becomes clear, and prepare solution A;

[0077] Weigh 0.1 g of octyl glucoside and dissolve it in 50 g of deionized water until it is completely dissolved, thereby preparing a solution B;

[0078] Under stirring conditions (speed of 600 rpm), 500 g of aluminum sol (BRD-300A nano aluminum sol produced by Suzhou Baird New Material Technology Co., Ltd., with an aluminum oxide mass content of 20%, a pH value of 2-5, and a particle size of 10-40 nm) and the solution A obtained in the first step were added to the solution B, and the mixture was heated to 70° C. and stirred (speed of 600 rpm) for 10 hours to obtain a mixed solution;

[0079] The stirred mixed solution was transferred into a crystallization kettle, crystallized at 200°C for 10 hours, taken out, quenched, and filtered to obtain the original alumina carrier powder;

[0080] The alumina carrier raw powder was washed, dried in a drying oven at 100°C for 10 hours, and calcined in air atmosphere at 500°C for 4 hours to obtain a mesoporous composite alumina carrier.

[0081] The specific surface area and pore volume of the mesoporous composite alumina carrier prepared in this comparative example are shown in Table 1.

[0082] Comparative Example 3

[0083] This comparative example provides a mesoporous composite alumina carrier.

[0084] The preparation method of the mesoporous composite alumina carrier provided in this comparative example is different from that in Example 1 in that octadecyl diester ammonium chloride (purchased from Henan Daochun New Material Technology Co., Ltd., model YH-866) and octyl glucoside are not added. The mesoporous composite alumina carrier is prepared by the following preparation method:

[0085] Weigh 1.00 g of aluminum acetylacetonate and 0.02 g of anhydrous zinc acetate compound, dissolve them in 100 g of ethanol in sequence, stir evenly until the solution becomes clear, and prepare solution A;

[0086] Weigh 50 g of deionized water, record as solution B;

[0087] Under stirring conditions (speed of 600 rpm), 500 g of aluminum sol (BRD-300A nano aluminum sol produced by Suzhou Baird New Material Technology Co., Ltd., with an aluminum oxide mass content of 20%, a pH value of 2-5, and a particle size of 10-40 nm) and the solution A obtained in the first step were added to the solution B, and the mixture was heated to 70° C. and stirred (speed of 600 rpm) for 10 hours to obtain a mixed solution;

[0088] The stirred mixed solution was transferred into a crystallization kettle, crystallized at 200°C for 10 hours, taken out, quenched, and filtered to obtain the original alumina carrier powder;

[0089] The alumina carrier raw powder was washed, dried in a drying oven at 100°C for 10 hours, and calcined in air atmosphere at 500°C for 4 hours to obtain a mesoporous composite alumina carrier.

[0090] The specific surface area and pore volume of the mesoporous composite alumina carrier prepared in this comparative example are shown in Table 1.

[0091] Comparative Example 4

[0092] This comparative example provides a mesoporous composite alumina carrier.

[0093] The preparation method of the mesoporous composite alumina carrier provided in this comparative example is different from that in Example 1 in that anhydrous zinc acetate is not added. The mesoporous composite alumina carrier is prepared by the following preparation method:

[0094] Weigh 1.00 g of aluminum acetylacetonate and dissolve it in 100 g of ethanol, stir evenly until the solution becomes clear, and prepare solution A;

[0095] Weigh 0.1 g of octyl glucoside and 0.1 g of octadecyl diacetyl ammonium chloride (purchased from Henan Daochun New Material Technology Co., Ltd., model YH-866) and dissolve them in 50 g of deionized water until they are completely dissolved, thereby preparing a solution B;

[0096] Under stirring conditions (speed of 600 rpm), 500 g of aluminum sol (BRD-300A nano aluminum sol produced by Suzhou Baird New Material Technology Co., Ltd., with an aluminum oxide mass content of 20%, a pH value of 2-5, and a particle size of 10-40 nm) and the solution A obtained in the first step were added to the solution B, and the mixture was heated to 70° C. and stirred (speed of 600 rpm) for 10 hours to obtain a mixed solution;

[0097] The stirred mixed solution was transferred into a crystallization kettle, crystallized at 200°C for 10 hours, taken out, quenched, and filtered to obtain the original alumina carrier powder;

[0098] The alumina carrier raw powder was washed, dried in a drying oven at 100°C for 10 hours, and calcined in air atmosphere at 500°C for 4 hours to obtain a mesoporous composite alumina carrier.

[0099] The specific surface area and pore volume of the mesoporous composite alumina carrier prepared in this comparative example are shown in Table 1.

[0100] Comparative Example 5

[0101] This comparative example provides a mesoporous composite alumina carrier.

[0102] The preparation method of the mesoporous composite alumina carrier provided in this comparative example is different from that in Example 1 in that aluminum nitrate is used instead of aluminum acetylacetonate. The mesoporous composite alumina carrier is prepared by the following preparation method:

[0103] Weigh 1.00 g of aluminum oxide and 0.02 g of anhydrous zinc acetate compound and dissolve them in 100 g of ethanol in sequence, stir evenly until the solution becomes clear, and prepare solution A;

[0104] Weigh 0.1 g of octyl glucoside and 0.1 g of octadecyl diacetyl ammonium chloride (purchased from Henan Daochun New Material Technology Co., Ltd., model YH-866) and dissolve them in 50 g of deionized water until they are completely dissolved, thereby preparing a solution B;

[0105] Under stirring conditions (speed of 600 rpm), 500 g of aluminum sol (BRD-300A nano aluminum sol produced by Suzhou Baird New Material Technology Co., Ltd., with an aluminum oxide mass content of 20%, a pH value of 2-5, and a particle size of 10-40 nm) and the solution A obtained in the first step were added to the solution B, and the mixture was heated to 70° C. and stirred (speed of 600 rpm) for 10 hours to obtain a mixed solution;

[0106] The stirred mixed solution was transferred into a crystallization kettle, crystallized at 200°C for 10 hours, taken out, quenched, and filtered to obtain the original alumina carrier powder;

[0107] The alumina carrier raw powder was washed, dried in a drying oven at 100°C for 10 hours, and calcined in air atmosphere at 500°C for 4 hours to obtain a mesoporous composite alumina carrier.

[0108] The specific surface area and pore volume of the mesoporous composite alumina carrier prepared in this comparative example are shown in Table 1.

[0109] Comparative Example 6

[0110] This comparative example provides a mesoporous composite alumina carrier.

[0111] The preparation method of the mesoporous composite alumina carrier provided in this comparative example is different from that in Example 1 in that: solution A is first mixed with solution B before adding the aluminum sol. The mesoporous composite alumina carrier is prepared by the following preparation method:

[0112] Weigh 1.00 g of aluminum acetylacetonate and 0.02 g of anhydrous zinc acetate compound, dissolve them in 100 g of ethanol in sequence, stir evenly until the solution becomes clear, and prepare solution A;

[0113] Weigh 0.1 g of octyl glucoside and 0.1 g of octadecyl diacetyl ammonium chloride (purchased from Henan Daochun New Material Technology Co., Ltd., model YH-866) and dissolve them in 50 g of deionized water until they are completely dissolved, thereby preparing a solution B;

[0114] After solution A and solution B are mixed, 500 g of aluminum sol (BRD-300A nano aluminum sol produced by Suzhou Baird New Material Technology Co., Ltd., with an aluminum oxide mass content of 20%, a pH value of the aluminum sol of 2-5, and a particle size of the aluminum sol of 10-40 nm) is added under stirring (rotation speed of 600 rpm), the temperature is raised to 70° C. and stirred (rotation speed of 600 rpm) for 10 hours to obtain a mixed solution;

[0115] The stirred mixed solution was transferred into a crystallization kettle, crystallized at 200°C for 10 hours, taken out, quenched, and filtered to obtain the original alumina carrier powder;

[0116] The alumina carrier raw powder was washed, dried in a drying oven at 100°C for 10 hours, and calcined in air atmosphere at 500°C for 4 hours to obtain a mesoporous composite alumina carrier.

[0117] The specific surface area and pore volume of the mesoporous composite alumina carrier prepared in this comparative example are shown in Table 1.

[0118] Comparative Example 7

[0119] This comparative example provides a mesoporous composite alumina carrier.

[0120] The preparation method of the mesoporous composite alumina carrier provided in this comparative example is different from that in Example 1 in that no crystallization is performed. The mesoporous composite alumina carrier is prepared by the following preparation method:

[0121] Weigh 1.00 g of aluminum acetylacetonate and 0.02 g of anhydrous zinc acetate compound, dissolve them in 100 g of ethanol in sequence, stir evenly until the solution becomes clear, and prepare solution A;

[0122] Weigh 0.1 g of octyl glucoside and 0.1 g of octadecyl diacetyl ammonium chloride (purchased from Henan Daochun New Material Technology Co., Ltd., model YH-866) and dissolve them in 50 g of deionized water until they are completely dissolved, thereby preparing a solution B;

[0123] Under stirring conditions (speed of 600 rpm), 500 g of aluminum sol (BRD-300A nano aluminum sol produced by Suzhou Baird New Material Technology Co., Ltd., with an aluminum oxide mass content of 20%, a pH value of 2-5, and a particle size of 10-40 nm) and the solution A obtained in the first step were added to the solution B, and the mixture was heated to 70° C. and stirred (speed of 600 rpm) for 10 hours to obtain a mixed solution;

[0124] The stirred mixed solution is filtered to obtain the alumina carrier raw powder;

[0125] The alumina carrier raw powder was washed, dried in a drying oven at 100°C for 10 hours, and calcined in air atmosphere at 500°C for 4 hours to obtain a mesoporous composite alumina carrier.

[0126] The specific surface area and pore volume of the mesoporous composite alumina carrier prepared in this comparative example are shown in Table 1.

[0127] Example 2

[0128] This embodiment provides a mesoporous composite alumina carrier.

[0129] The mesoporous composite alumina carrier provided in this embodiment is prepared by the following preparation method:

[0130] Weigh 1.00 g of aluminum acetylacetonate and 0.05 g of anhydrous zinc acetate compound, dissolve them in 60 g of ethanol in sequence, stir evenly until the solution becomes clear, and prepare solution A;

[0131] Weigh 0.01 g of dodecyl glucoside and 0.08 g of hexadecyl diacetyl ammonium chloride (purchased from Henan Daochun New Material Technology Co., Ltd.) and dissolve them in 100 g of deionized water until they are completely dissolved, thereby preparing a solution B;

[0132] Under stirring (rotation speed of 600 rpm), 400 g of aluminum sol (JR14W nano aluminum sol of Xuancheng Jingrui New Materials Co., Ltd., with an aluminum oxide mass content of 20%, a pH value of 2-5, and a particle size of 10-40 nm) and the solution A obtained in the first step were added to the solution B, and the mixture was heated to 60° C. and stirred (rotation speed of 600 rpm) for 20 hours to obtain a mixed solution;

[0133] The stirred mixed solution was transferred into a crystallization kettle, crystallized at 100°C for 72 hours, taken out, quenched, and filtered to obtain the original alumina carrier powder;

[0134] The alumina carrier raw powder was washed, placed in a drying oven and dried at 150°C for 8 hours, and calcined at 550°C in air atmosphere for 6 hours to obtain a mesoporous composite alumina carrier.

[0135] The specific surface area and pore volume of the mesoporous composite alumina carrier prepared in this example are shown in Table 1.

[0136] Example 3

[0137] This embodiment provides a mesoporous composite alumina carrier.

[0138] The mesoporous composite alumina carrier provided in this embodiment is prepared by the following preparation method:

[0139] Weigh 1.00 g of aluminum acetylacetonate and 0.08 g of anhydrous zinc acetate compound, dissolve them in 90 g of ethanol in sequence, stir evenly until the solution becomes clear, and prepare solution A;

[0140] Weigh 0.05 g of dodecyl glucoside and 0.01 g of dodecyl diester ammonium chloride (purchased from Henan Daochun New Material Technology Co., Ltd.) and dissolve them in 100 g of deionized water until they are completely dissolved, thereby preparing a solution B;

[0141] Under stirring (speed of 1000 rpm), 100 g of aluminum sol (MST-LRJ20 nano aluminum sol of Huzhou Mister New Materials Co., Ltd., with an aluminum oxide mass content of 20%, a pH value of 2-5, and a particle size of 10-40 nm) and the solution A obtained in the first step were added to the solution B, and the temperature was raised to 80° C. and stirred (speed of 1000 rpm) for 20 hours to obtain a mixed solution;

[0142] The stirred mixed solution was transferred into a crystallization kettle, and after crystallization at 240°C for 6 hours, it was taken out, quenched, and filtered to obtain the original alumina carrier powder;

[0143] The alumina carrier raw powder was washed, placed in a drying oven and dried at 80°C for 20 hours, and calcined at 600°C in air atmosphere for 4 hours to obtain a mesoporous composite alumina carrier.

[0144] The specific surface area and pore volume of the mesoporous composite alumina carrier prepared in this example are shown in Table 1.

[0145] Example 4

[0146] This embodiment provides a mesoporous composite alumina carrier.

[0147] The mesoporous composite alumina carrier provided in this embodiment is prepared by the following preparation method:

[0148] Weigh 1.00 g of aluminum acetylacetonate and 0.12 g of anhydrous zinc acetate compound and dissolve them in 140 g of ethanol in sequence, stir evenly until the solution becomes clear, and prepare solution A;

[0149] Weigh 0.005 g of dodecyl glucoside and 0.05 g of dodecyl diester ammonium chloride (purchased from Henan Daochun New Material Technology Co., Ltd.) and dissolve them in 20 g of deionized water until they are completely dissolved, thereby preparing a solution B;

[0150] Under stirring (rotation speed of 800 rpm), 150 g of aluminum sol (CY-L01A nano aluminum sol produced by Hangzhou Jiupeng New Materials Co., Ltd., with an aluminum oxide mass content of 20%, a pH value of 2-5, and a particle size of 10-40 nm) and the solution A obtained in the first step were added to the solution B, and the mixture was heated to 70° C. and stirred (rotation speed of 800 rpm) for 15 hours to obtain a mixed solution;

[0151] The stirred mixed solution was transferred into a crystallization kettle, and after crystallization at 160°C for 48 hours, it was taken out, quenched, and filtered to obtain the original alumina carrier powder;

[0152] The alumina carrier raw powder was washed, dried in a drying oven at 120° C. for 15 hours, and calcined in air atmosphere at 500° C. for 8 hours to obtain a mesoporous composite alumina carrier.

[0153] The specific surface area and pore volume of the mesoporous composite alumina carrier prepared in this example are shown in Table 1.

[0154] Application Example 1

[0155] The mesoporous composite alumina carriers provided in Examples 1 to 4 and Comparative Examples 1 to 7 were loaded with metal Pt and then used in propane dehydrogenation reactions.

[0156] The mesoporous composite alumina carrier is loaded with metal Pt by an equal volume impregnation loading method, and the Pt loading amount is 0.4% of the mass of the mesoporous composite alumina carrier. The precursor of Pt during the impregnation is chloroplatinic acid (reagent grade, Shanghai Bojing Chemical Co., Ltd.).

[0157] Propane dehydrogenation reaction was carried out in a fixed bed microreactor. The specific process conditions were as follows: 620°C, GHSV = 2000h -1 , atmospheric pressure, catalyst loading 1.0g. The evaluation results are shown in Table 2.

[0158] Table 1 Specific surface area and pore volume data of samples

[0159]

[0160] Table 2 Propane dehydrogenation reaction data of samples

[0161]

[0162]

[0163] Application Example 2

[0164] The mesoporous composite alumina carriers provided in Example 1 and Comparative Example 3 were tested by transmission electron microscopy. The results are as follows: Figure 1 , Figure 2 shown.

[0165] The mesoporous composite alumina carriers provided in Example 1, Example 2, Example 3, Example 4 and Comparative Example 3 were tested by XRD spectra. The results are as follows: Figure 3 , Figure 4 shown.

[0166] The embodiments described above are for better explaining the present invention. For technical researchers in the field, it is not difficult to make various modifications to these embodiments without departing from the principles and spirit of the present invention. Therefore, the present invention is not limited to the embodiments herein. The improvements and changes made by those skilled in the art to the present invention according to the principles and spirit of the present invention should be within the protection scope of the present invention.

Claims

1. A method for preparing a mesoporous composite alumina carrier, wherein: The preparation method comprises: Aluminum acetylacetonate and zinc acetate are dissolved in an alcohol solvent to obtain solution A; Dissolving alkyl glucoside and alkyl diester quaternary ammonium salt in water to obtain solution B; Adding aluminum sol and solution A to solution B simultaneously for crystallization to prepare alumina carrier raw powder; The raw powder of alumina carrier is post-treated to obtain a mesoporous composite alumina carrier.

2. The preparation method according to claim 1, wherein The mass ratio of aluminum acetylacetonate, zinc acetate, alcohol solvent, alkyl glucoside, alkyl diester quaternary ammonium salt, aluminum sol and water is: aluminum acetylacetonate: zinc acetate: alcohol solvent: alkyl glucoside: alkyl diester quaternary ammonium salt: aluminum sol: water = 1: (0.01-0.5): (50-150): (0.005-0.1): (0.005-0.1): (10-500): (50-200).

3. The preparation method according to claim 1, wherein The mass content of aluminum oxide in the aluminum sol is 10-50%; The pH value of aluminum sol is 2-5; The particle size of aluminum sol is 10-40nm; The alcohol solvent is methanol or ethanol.

4. The preparation method according to claim 1, wherein The alkyl group of the alkyl glucoside is a C8-C18 chain alkyl group; Preferably, the alkyl glucoside is selected from at least one of hexyl glucoside and octyl glucoside.

5. The preparation method according to claim 1, wherein The alkyl group of the alkyl diester quaternary ammonium salt is a C8-C18 chain alkyl group; Preferably, the alkyl diester-based quaternary ammonium salt is selected from at least one of dodecyl diester-based quaternary ammonium salt, tetradecyl diester-based quaternary ammonium salt, and hexadecyl diester-based quaternary ammonium salt.

6. The preparation method according to claim 1, wherein Adding aluminum sol and solution A to solution B simultaneously for crystallization to prepare alumina carrier raw powder includes: Add aluminum sol and solution A to solution B simultaneously under stirring conditions, heat and stir to obtain a mixed solution; The mixed solution is subjected to crystallization treatment; The product obtained by the crystallization treatment is cooled and then solid-liquid separation is performed, and the obtained solid phase is the original powder of the alumina carrier; Preferably, the temperature of heating and stirring is 60-80°C; Preferably, the heating and stirring time is 4-20 hours; Preferably, the stirring speed of the heating stirring is 200-1000 r / min; Preferably, when the aluminum sol and solution A are added to solution B simultaneously under stirring conditions, the stirring speed is 600-1000 r / min.

7. The preparation method according to claim 1 or 6, wherein: The crystallization temperature is 100-250°C; The crystallization time is 6-72 hours.

8. The preparation method according to claim 1, wherein The mesoporous composite alumina carrier obtained by post-processing the original alumina carrier powder includes: The alumina carrier raw powder is washed, dried and calcined in sequence to obtain a mesoporous composite alumina carrier; Preferably, the drying temperature is 80-150°C; Preferably, the calcination temperature is 450-600°C; Preferably, the calcination time is 4-10 hours; Preferably, the calcination atmosphere is an air atmosphere.

9. A mesoporous composite alumina carrier, which can be prepared by the preparation method of the mesoporous composite alumina carrier according to any one of claims 1 to 8.

10. Use of the mesoporous composite alumina carrier according to claim 9 in alkane dehydrogenation and olefin saturation hydrogenation.

Citation Information

Patent Citations

  • Macroporous-mesoporous alumina as well as preparation method and application of macroporous-mesoporous alumina

    CN108640132A

  • Preparation method of high specific surface area mesoporous alumina

    CN108862345A